Practices and performance outcomes of green supply chain management initiatives in the garment industry. Issue 4 (22nd February 2022) - Habib, Mohammad Ahsan; Balasubramanian, Sreejith; Shukla, Vinaya; Chitakunye, David; Chanchaichujit, Janya
Abstract : Purpose: The garments/textiles industry is the second most polluting industry in the world. However, efforts to understand and curtail its adverse environmental impacts have not been commensurate, and previous works have largely been fragmented and disjointed. This study aims to coduct a comprehensive and systematic green supply chain management (GSCM) investigation on this industry, where a multidimensional framework involving green supply chain practices and performance is developed, validated and applied. Design/methodology/approach: A framework consisting of 12 constructs (8 on practices and 4 on performance) and their underlying measures were developed through an extensive literature review. A survey methodology was used to obtain responses from 403 garment-manufacturing firms in Bangladesh, one of the leading garment producers in the world. Confirmatory factor analysis and structural equation modeling were used first to validate the first- and second-order constructs and then test the hypothesized relationships. Findings: Internal environmental management and cooperation with stakeholders were identified as necessary precursors for implementing the second-order green supply chain practices comprising green design, green purchasing, green manufacturing, green transportation, green facilities and end-of-life management. The implementation of green supply chain practices was found to have a (direct) positive impact on environmental, economic and operational performance and an indirect positive impact on organizational performance. Similarly, both economic and operational performance was found to impact organizational performance positively. Surprisingly, a negative relationship (albeit low) was observed between environmental and organizational performance. Also, garment-manufacturing firms were found to have been unable to translate their IEM capabilities into strategic and long-term cooperation with stakeholders. Research limitations/implications: The study fills a gap in the literature about applying/implementing GSCM in the garment industry. Future studies in the garment industry and elsewhere could utilize the framework to understand further the synergistic impact of green supply chain practices on performance. Practical implications: The findings provide practitioners, policymakers and organizations associated with the garment industry with critical insights on the various opportunities and challenges in adopting GSCM. Also, the positive impact of green supply chain practices on performance could provide the impetus for manufacturing firms to adopt GSCM. Originality/value: A comprehensive GSCM investigation on the garment industry has not been previously attempted and constitutes the novelty of this work. Also, Bangladesh is the second-largest garment exporter worldwide, making this study contribution even more valuable.